26.9k views
3 votes
Please help quickly :3 thanks

Please help quickly :3 thanks-example-1
Please help quickly :3 thanks-example-1
Please help quickly :3 thanks-example-2
User EddieBytes
by
5.7k points

2 Answers

5 votes

Answer one,

x = 5

Explanation One,

6 x 5 - 2 = 5 x 5 + 3

30 - 2 = 25 + 3

28 = 28


Answer Two,

A, C, F

Explanation Two,

3/3 + 5 = 6

1 + 5 = 6

So, A is correct,

2 x 3 + 4 = 10

6 + 4 = 10

So, C is correct,

9 - 3 x 3 = 0

9 - 9 = 0

So, F is correct


Hope this helps :-)

User Mikayel Ghazaryan
by
6.3k points
6 votes

6x - 2 = 5x + 3 6x - 5x = 3 + 2 X = 5 9 - 3x = 0 9 = 3x X = 9/3 X = 3

User Study
by
5.9k points